REQUIREMENTS FOR TEACHER SKILLS AND WAYS TO ENSURING THEIR PRACTICAL IMPLEMENTATION (Universal International Scientific Journal, 2026)
This article discusses modern requirements for qualified teachers, ways to form and develop their professional competencies, as well as how these requirements are implemented in practice. It also analyzes innovative approaches, state policy, and the role of the education system in increasing the effectiveness of pedagogical activities.
Keywords: pedagogical skills, professional competence, modern requirements, education system, practical implementation, innovative approach